AN ENHANCE DESIGN HEATING BIODIESEL PRODUCTION FROM OIL BASED ON ARDUINO MEGA - Solly Aryza; Pristisal Wibowo; Deni Saputra (INFOKUM, 2022)
Biodiesel energy is one of the alternative energies in the current era of global warming, which is needed by the community to meet renewable energy in electrical energy but is constrained by the unavailability of electricity which so far has only relied on PLN as a national electricity source. Especially the people who are in the interior who do not get electricity from PLN, while electricity has now become a primary need, which means that the community at this time must be served by electricity. Considering that Indonesia is the largest producer of palm oil in the world today, so the waste left behind is also getting bigger. This research was conducted to take advantage of this by utilizing waste, namely used cooking oil which is converted into biodiesel which will be used as fuel for Diesel Power Plants (PLTD). This research produces biodiesel B-100, which means the biodiesel is pure without a mixture of petroleum, by designing an automatic biodiesel processing device based on Arduino Mega. This study also analyzes how feasible B-100 biodiesel is for use in diesel-powered generators, by looking at the economic aspect, and of course also in the electronics aspect